PENERAPAN DIVERSI TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM MENURUT QANUN ACEH NOMOR 9 TAHUN 2008 TENTANG PEMBINAAN KEHIDUPAN ADAT DAN ADAT ISTIADAT DAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Madiasa Ablisar; Marlina; Edy Ikhsan; Maulana Muslim Hrp (Jurnal Hukum Samudra Keadilan, 2021)
The background is by two law applications that apply in Aceh, the first law that generally applies in Indonesia and the second one that applies specifically in Aceh, the Law Number 11 of 2012 concerning the System Juvenile Criminal Court is a way out for better handling of children conflict with the law. The law regulates diversion where there are two important things that have a special place in the SPPA Law, namely restorative justice and diversion. The results showed that the resolution of the problem of children conflict with the law in Aceh consists of two legal applications, starting with the mediation process according to Aceh Qanun Number 9 of 2008 concerning fostering customary life and customs Development with the aim that these problems can be resolved amicably according to the Decree Joint between the Governor of Aceh and the Aceh Regional Police and the Aceh Traditional Council No 189/677/2011 dated 20 December 2011 concerning the Implementation of the Gampong and Mukim Adat Courts, but if during the mediation process no agreement is found then proceed to the legal process according to the Law Number 11 of 2012 concerning the Criminal Justice System for Children.